Sistema para análise de marcha online baseado e IMUs - Rosa, Anderson Sachetto (2017)
A clinical evaluation of functional gait capacity often occurs subjectively, based on the clinical practitioner’s experience and descriptive information on standard movement. This M.Sc. Dissertation describe the development of a system to online gait analysis, provided with a Graphcal User interface, able to supply these professionals with quantity informations about the kinematics of patient gait during the moviment execution. A database module has been developed to record the patiente gait parammeters during its daily live, with possibilitie further analysis by the clinical proffetional using the same system. The online operation was ensured, since the processing, from the acquisition of the sample to its on-screen display,is done before of a new sample be received by the data acquisition system. The system tests was divided in two sections, with two repetitions each one, and the subjects was placed to walk in a treadmill. In the first section, 10 stride with the right leg was obtained for each subject, to evaluate the system capacity in to delimit the gait cicles. In the second, each subject gait by one minute, to available the processing data system during the time. To gait kinematics estimate, aim of this work, its very important to detect the HS (Heel Strike) and TO (Toe Off) events, during the gait execution. This task was correctly executed in 94